PTU-112 Hepatology outreach services to overcome inequalities in hepatitis c care in an isolated uk population. (22nd June 2015) - Buchanan, R; Shalabi, A; Grellier, L; Parkes, J; Khakoo, S
Abstract : Introduction: Increasingly effective treatments for Hepatitis C virus (HCV) infection are unlikely to have a significant impact on disease prevalence unless barriers to specialist care and treatment are overcome. The Isle of Wight (IOW) is situated 3 miles off the coast of the UK and is without a local HCV treatment service. The aims of this study are to compare the care outcomes in patients with HCV living in this isolated community to a nearby mainland cohort and describe the initial impact of a hepatology outreach service to the island. Method: The medical records of a representative 77 HCV patients from the IOW were compared to a random sample of 79 patients from Southampton City. Patients from the IOW who had been diagnosed by the drug support or sexual health services, but had never been seen by a Hepatology specialist, were contacted and invited to community based Hepatology outreach clinics. Results: Patients from the IOW were older (p 0.007) and had a significantly higher prevalence of liver cirrhosis (p 0.01). Significantly more patients with HCV had died from liver disease on the IOW (p 0.03), although similar numbers had been treated (p 0.57) (Table 1 ). Those patients who were seen in hepatology clinics were reviewed in a similar time frame with 79% of IOW and 89% of Southampton patients being seen within 1 year of diagnosis (p 0.33). 14 patients on the IOW have been invited to 3 community outreach clinics in the sexual health and drug and alcohol support centres. Of these 7 attended, 3 have subsequently been referred for treatment, with 3 declining due to the distance and cost of travel to the mainland. Conclusion: The IOW has a higher prevalence of advanced liver disease with excess mortality. In an attempt to address this inequality outreach clinics have been established and have initially proved effective at re-engaging patients with a known diagnosis of HCV into specialist care. However, in an isolated community the effectiveness of this will be limited without the provision of community-based treatment. Disclosure of interest: R. Buchanan Grant/ Research Support from: Gilead Fellowship 2014, A. Shalabi: None Declared, L. Grellier: None Declared, J. Parkes: None Declared, S. Khakoo: None Declared.